2017
DOI: 10.1016/j.fertnstert.2017.07.1168
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the use of assisted reproductive technology in the United States by non–United States residents

Abstract: This analysis showed that non-U.S. resident cycles accounted for a growing share of all U.S. ART cycles and made higher use of specialized treatment techniques. This study provides important baseline data on CBRC in the U.S. and may also prove to be useful to organizations interested in improving access to fertility treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Despite controversies from medical and ethical perspectives, this is unavoidable in the globalizing world . Data from Europe and America suggested that about 3–5% of ART activities carried out in recent years involved cross‐border patients . It is certainly worthwhile to look into such data in our region in future surveys.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Despite controversies from medical and ethical perspectives, this is unavoidable in the globalizing world . Data from Europe and America suggested that about 3–5% of ART activities carried out in recent years involved cross‐border patients . It is certainly worthwhile to look into such data in our region in future surveys.…”
Section: Discussionmentioning
confidence: 93%
“…4,5 Data from Europe and America suggested that about 3-5% of ART activities carried out in recent years involved cross-border patients. [5][6][7] It is certainly worthwhile to look into such data in our region in future surveys.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important question because the U.S. has become a popular destination for cross-border reproductive care. In the 8-year period from 2006 to 2013, residents of 147 other countries underwent assisted reproduction in the U.S. (5).…”
mentioning
confidence: 99%
“…In another major study from North America, it was estimated that approximately 4% of patients treated with IVF in the USA were from other countries (Hughes et al, 2016;Hughes and DeJean, 2010), and that 6% of Canadian IVF patients left their country for treatment, including to the USA, mostly for donor oocytes (80%). A recent detailed analysis of the extent and scope of reproductive travel to the USA shows a doubling of incoming patients over the 7-year reporting period from 2006 to 2013 (Levine et al, 2017). Using data from the US Centers for Disease Control and Prevention's National ART Surveillance System, the study shows that 1.2% of all ART cycles performed in 2006 were for non-US residents, but that the number increased to 2.8% of all ART cycles in 2013.…”
Section: Transnational Questsmentioning
confidence: 94%